PENGUNGKAPAN PRAKTIK SDM DAN KINERJA PASAR PERUSAHAAN - Sasikirono, Nugroho; Kurniawan, Adimas Yahya; Julianti, Praptini; Meidiaswati, Harlina (Universitas Negeri Surabaya, 2024)
This study aims to determine the effect of HRM practices on company market performance. HRM practice is proxied by the HRM Practice Disclosure Index (HRMPI). We utilise content analysis techniques to measure HRMPI. Tobin's Q. measures the company's market performance. We utilise purposive sampling, using multiple linear regression as the analysis method. The total sample size is 186 public companies listed on the Indonesia Stock Exchange (IDX) during 2014-2018, with 854 observations. The results show that HRM practice has a positive relationship with the company's market performance. The company's ability to implement HRM Practices has positive implications for the company's human capital. Companies with a higher HRMPI can better create a competitive advantage. This encourages the company's performance to be better and leads to an increase in the market value. Robustness checks using the dimensions of the HRM Practice Index, the alternative performance measures, and the endogeneity test bring consistent results.